Sri Lanka Ending Poverty and Promoting Shared Prosperity : A Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2016)
Sri Lanka is in many respects a development success story. With economic growth averaging more than 7 percent a year over the past five years on top of an average growth of 6 percent the preceding five years, Sri Lanka has made notable strides towards the goals of ending extreme poverty and promoting shared prosperity (the ‘twin goals’). The national poverty headcount rate declined from 22.7 to 6.7 percent between 2002 and 2012/13, while consumption per capita of the bottom 40 percent grew at 3.3 percent a year, compared to 2.8 percent for the total population. Other human development indicators are also impressive by regional and lower middle-income country standards. Sri Lanka has also succeeded in ending decades of internal conflict in 2009 and steps have been taken towards reconciliation. Sri Lanka’s has had impressive development gains but there are strong indications that drivers of past progress are not sustainable. Solid economic growth, strong poverty reduction, overcoming internal conflict, effecting a remarkable democratic transition in recent months, and overall strong human development outcomes are a track record that would make any country proud. However, the country’s inward looking growth model based on non-tradable sectors and domestic demand amplified by public investment cannot be expected to lead to sustained inclusive growth going forward. A systematic diagnostic points to fiscal, competitiveness, and inclusion challenges as well as cross-cutting governance and sustainability challenges as priority areas of focus for sustaining progress in ending poverty and promoting shared prosperity.